Avaliação da atividade de neutrófilos em ratos Wistar (Rattus norvegicus) tratados com quefir - Zolini, Guilherme Pimenta de Padua (2006)
This work was carried out in the Microorganism Fisiology Biology and Phytopharmacy laboratories of the José do Rosário Vellano University (UNIFENAS) The aim of the study was to evaluate some aspects related to the immunitary activity of neutrophils in rats treated with kefir a probiotic made from various microorganisms The tests were conducted to determine the level of cytokine TNF-alpha cell recruiting cellular metabolism neutrophils oxygen consumption hydrogen peroxide formation by neutrophils screening for myeloperoxidase positive neutrophils and assay of redox titration The tested groups consisted of albino male Wistar rats the test group received 1,0 ml of kefir solution the negative control received 1,0 ml of saline solution (NaCl 0,9 %) and the positive control received 100 mg/kg of tocopherol (Vit E) except for those on TNF-alpha and cell recruiting in which the positive control received 0,5 mg/kg of dexamethasone by 7 days gavage except for redox assay where the groups did not consist of animals The results were analyzed by means +- SEM using comparison test of Student Newman Keuls (SNK) except for respirometry assay for which t Student test was used Significant differences were found in kefir and negative control groups in cell recruiting assays (P<0,05) hydrogen peroxide formation stimulated by forbol ester (P<0,05) and identification of myeloperoxidase (P<0,01) given that both previously mentioned had the same index shown by the positive control For the cell recruiting assay the kefir the positive control and the negative control groups presented 12,0 +- 1,0 x 106, 7,3 +- 1,4 x 106 and 17,2 +- 1,9 x 106 neutrophils/mL respectively On the other hand in the hydrogen peroxide formation stimulated by forbol ester the kefir and the positive control groups presented averages of 1,46 +- 0,16 e 1,50 +- 0,22 femtomol/cell respectively showing no difference The negative control at 2,14 +- 0,18 femtomol/cell was considered statistically different from the kefir group In the assay for myeloperoxidase identification kefir and positive control groups were considered identical with indexes of 54,8 +- 3,0 % 47,3 +- 5,7 % respectively different from the negative control group with index of 74,0 +- 1,9 % positive MPO The other assays did not show significant effects In conclusion the ingestion of kefir was capable of diminishing cell recruiting inhibiting H2O2 production and suggests the reduction of the activity of MPO in the neutrophils